2020
DOI: 10.20961/stjssa.v17i1.41396
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the accuracy of estimating soil moisture using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI)

Abstract: <span>The Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI) are used to monitor and identify different types of drought, including meteorological, hydrological, and agricultural droughts. This study evaluates the accuracy of estimating soil moisture levels using the two indexes. The analysis correlated the SPI and the SPEI over three years (November 2016–October 2019) using <em>Rstudio</em>, with average monthly soil moisture tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was shown that short timescales (1 or 3 months) can be used to describe meteorological drought while a 3-month or 6-month scale is usually used to evaluate an agricultural drought, and a longer scale, such as 12 or 24 months, is more suitable for investigating hydrological drought and water resources (Mishra and Singh 2010;Pei et al 2020). For example, the SPEI index for a 6-month scale, calculated for a timeseries in Indonesia presented the best accuracy for modeling soil moisture (95%) compared to the rest of the timescales used (3-, 6-,12-months) (Ariyanto et al 2020). Nevertheless, the type of the soil was Alfisol, which has a clay texture and very stable aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that short timescales (1 or 3 months) can be used to describe meteorological drought while a 3-month or 6-month scale is usually used to evaluate an agricultural drought, and a longer scale, such as 12 or 24 months, is more suitable for investigating hydrological drought and water resources (Mishra and Singh 2010;Pei et al 2020). For example, the SPEI index for a 6-month scale, calculated for a timeseries in Indonesia presented the best accuracy for modeling soil moisture (95%) compared to the rest of the timescales used (3-, 6-,12-months) (Ariyanto et al 2020). Nevertheless, the type of the soil was Alfisol, which has a clay texture and very stable aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the precipitation single-dependence indices is that they neglect the role of temperature in increasing water loss through enhanced evaporation [20][21][22] and the impact of global warming on drought characteristics 23,24 . Instead, indices that combine precipitation and temperature or atmospheric evaporative demand (AED) have been proposed and have proven effective in drought detection 17,[25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%